Developmental axon stretch stimulates neuron growth while maintaining normal electrical activity, intracellular calcium flux, and somatic morphology - Loverde, Joseph R.; Pfister, Bryan J. (Frontiers in Cellular Neuroscience, 2015)
Elongation of nerve fibers intuitively occurs throughout mammalian development, and is synchronized with expansion of the growing body. While most tissue systems enlarge through mitosis and differentiation, elongation of nerve fibers is remarkably unique. The emerging paradigm suggests that axons undergo stretch as contiguous tissues enlarge between the proximal and distal segments of spanning nerve fibers. While stretch is distinct from growth, tension is a known stimulus which regulates the growth of axons. Here, we hypothesized that the axon stretch-growth process may be a natural form of injury, whereby regenerative processes fortify elongating axons in order to prevent disconnection. Harnessing the live imaging capability of our axon stretch-growth bioreactors, we assessed neurons both during and following stretch for biomarkers associated with injury. Utilizing whole-cell patch clamp recording, we found no evidence of changes in spontaneous action potential activity or degradation of elicited action potentials during real-time axon stretch at strains of up to 18 % applied over 5 minutes. Unlike traumatic axonal injury, functional calcium imaging of the soma revealed no shifts in free intracellular calcium during axon stretch. Finally, the cross-sectional areas of nuclei and cytoplasms were normal, with no evidence of chromatolysis following week-long stretch-growth limited to the lower of 25 % strain or 3 mm total daily stretch. The neuronal growth cascade coupled to stretch was concluded to be independent of the changes in membrane potential, action potential generation, or calcium flux associated with traumatic injury. While axon stretch-growth is likely to share overlap with regenerative processes, we conclude that developmental stretch is a distinct stimulus from traumatic axon injury.